Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan - Risma Nopianti; Suparno (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
This study aims to examine the effect of capital structure and profitability on firm value both partially and simultaneously. The capital structure variable (X1) is proxied by Debt Equity Ratio (DER), the Profitability Variable (X2) is proxied by Return On Equity (ROE) and Company Value (Y) is proxied by Price To Book Value (PBV). This type of research uses explanatory research with a quantitative approach, the population in the study are all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2018. With a purposive sampling technique with a sample size of 10 companies. The data obtained were analyzed by testing the validity of the data, multiple linear regression analysis, and hypothesis testing using the t test and f test. The results of this study indicate that capital structure has a positive and significant effect on firm value, profitability has a positive and significant effect on firm value, and capital structure and profitability together have a positive and significant effect on firm value. Keywords: capital structure, profitability, and firm value